PENGARUH KOMPETENSI AUDITOR TERHADAP KUALITAS AUDIT DIMEDIASI KOMITMEN ORGANISASI DI SEKTOR PUBLIK - Andreansyah Firman Maulana; Indrawati Yuhertiana (JURNAL ILMIAH EDUNOMIKA, 2021)
The purpose of this study was to examine the effect of auditor competence on audit quality with organizational commitment as a mediating variable. This research is quantitative research using primary data on auditors who work in the Inspectorate of East Java Province using purposive sampling method. A total of 51 questionnaires were distributed, only 33 questionnaires whose data could be processed and analyzed. Data analysis in this study used the Partial Least Square (PLS) technique with the WarpPLS statistical tool version 6.0. The results of the study prove that auditor competence has a significant effect on audit quality, organizational commitment has a significant effect on audit quality, and auditor competence has a positive effect on audit quality with organizational commitment as an intervening variable in the public sector. Keywords: auditor competence; audit quality; organizational commitment; APIP